Combined bioactive approach over atherosclerosis risk biomarkers - Scolaro, Bianca (2017)
Atherosclerosis, one major cause of morbidity and mortality worldwide, is a complex and multifactorial disease that involves three mainly conditions: chronic inflammation, dyslipidemia and oxidative stress. Although statins are the first-line therapy for LDL cholesterol (LDL-C) lowering, the efficacy of cardiovascular events prevention is limited to 30-40%. This residual risk brought attention to the need of new therapies and clinical targets beyond LDL-C, such as inflammation and oxidative stress. Importantly, suboptimal treatment and/or statin discontinuation due to adverse effects have also been a very challenging clinical problem. Complementary diet therapy can be an effective and safe approach to support pharmacological treatment, especially when drugs alone are insufficient to attenuate risk factors and/or the recommended dose is not well tolerated. The aim of this study was to evaluate the effects of three bioactive components, namely omega-3 fatty acids, plant sterols and polyphenols, on markers of dyslipidemia, inflammation and oxidative stress in patients treated with statins. A randomized, crossover clinical study was carried out, with the participation of 53 subjects. At each intervention period, study participants received a packaged for the functional or control treatment. Functional treatment consisted of fish oil (1.7 g of EPA+DHA/day), chocolate containing plant sterols (2.2 g/day) and green tea (two tea sachets/day). Control treatment consisted of soy oil softgels, regular chocolate and anise tea. After 6 weeks of intervention, functional treatment reduced plasma LDL-C (-13.7% ± 3.7, p=0.002) and C-reactive protein (-35.5% ± 5.9, p=0.027). Plasma triacylglycerol (-15.68% ± 5.94, p=0.02) and MDA (-40.98% ± 6.74, p=0.04) were reduced in subgroups of patients (n=23) with baseline values above the median (93 mg/dL and 2.23 umol/L, respectively). Analysis of lathosterol and campesterol in plasma suggested that intensity of LDL-C reduction was influenced by cholesterol absorption rate rather than its endogenous synthesis. After multivariate analysis, patients identified as \"good responders\" to supplementation (n=10) were recruited for a pilot protocol of statin dose reduction with complementary diet therapy. Responders received the functional treatment for 12 weeks: standard statin therapy was kept during the first 6 weeks and reduced by 50% from weeks 6 to 12. No difference was observed for plasma lipids and inflammation biomarkers, cholesterol efflux capacity or HDL particle number after statin dose reduction when compared to standard therapy. Although limited by the small sample size, our study demonstrates the potential for a new therapeutic approach combining lower statin dose and specific dietary compounds. This may be particularly helpful for the many patients with, and at risk for, CVD who cannot tolerate high-dose statin therapy.